Intensitas Komunikasi dan Keberhasilan Pemberdayaan Masarakat Berbasis Pendampingan di Desa Wisata Selasari-Kabupaten Pangandaran - Diana Simanjuntak (STIEPAR YAPARI Bandung, 2021)
This study aims to explore the intensity of communication and the success of mentoring-based community empowerment in the Selasari Tourist Village - Pangandaran Regency. This research was a qualitative descriptive with a case study approach. The research data collection techniques was through in-depth interviews, participatory observation, document studies and literature studies. The research informants were 20 people of the community of Selasari Tourism Village, Pangandaran Regency who had participated in a community empowerment program based on assistance. However, there were only 5 key informants selected consisted of tourist village managers, UMKM managers, homestay managers and tour guides as well as the Head of Selasari Village. The results showed that the four months intensity of communication between companions and participants greatly supported the success of community empowerment. It was evident from their ability to take part in the Indonesian Tourism Village Appreciation (ADWI) and Sustainable Tourism Village Certification competitions in 2021. Informants also explained that compared to community empowerment by various parties prior which did not bring much change for them, the assistance approach was very useful for their ability in developing their village. The intensity of communication carried out by the facilitators in the empowerment process consists of: the frequency of repeated communication, the duration of communication that describes the length of the meeting, the familial attention of the facilitators toward the community, regularity in communication in the form of a clear and definite schedule, the message breadth level and the limited number of participants in communication, and the message depth level. All the mentioned can encourage the community empowerment participants to achieve optimal mentoring results.